PTCHD1 gene mutation/deletion: the cognitive-behavioral phenotyping of four case reports - Montanaro, Federica Alice Maria; Mandarino, Alessandra; Alesi, Viola; Schwartz, Charles; Sepulveda, Daniela Judith Claps; Skinner, Cindy; Friez, Michael; Piccolo, Gabriele; Novelli, Antonio; Zanni, Ginevra; Dentici, Maria Lisa; Vicari, Stefano; et al. (Frontiers in Psychiatry, 2024)
X-linked PTCHD1 gene has recently been pointed as one of the most interesting candidates for the involvement in neurodevelopmental disorders (NDs), such as intellectual disability (ID) and autism spectrum disorder (ASD). PTCHD1 encodes the patched domain containing protein 1 (PTCHD1), which is mainly expressed in the developing brain and in adult brain tissues. To date, main research has focused on the biological function of PTCHD1 gene, while the mechanisms underlying neuronal alterations as well as the cognitive-behavioral phenotype associated with mutations remain still unclear.With the aim of incorporating information on the clinical profile of affected individuals and enhancing the characterization of the genotype-phenotype correlation, , here we analyze the clinical features of four individuals (two children and two adults) in which array-CGH detected a PTCHD1 deletion or in which panel for screening nonsyndromal XLID (X-linked ID) detected a PTCHD1 gene variant. We define the neuropsychological and psychopathological profiles, providing quantitative data from standardized evaluations. Assessment consisted of clinical observations, structured interviews, and parent/self-reported questionnaires. The results of our descriptive analysis align with previous findings on the involvement of the PTCHD1 gene in NDs. Specifically, our patients exhibited a clinical phenotype characterized by psychomotor developmental delay-ID of varying severity. Interestingly, while ID during early childhood was associated with autistic-like symptomatology, this interrelation was no longer observed in the adult subjects. Furthermore, our cohort did not display peculiar dysmorphic features, congenital abnormalities or comorbidity with epilepsy. In conclusion, our analysis shows that the psychopathological and behavioral comorbidities along with cognitive impairment interfere with development, therefore contributing to the severity of disability 2 This is a provisional file, not the final typeset article associated with PTCHD1 gene mutation. Awareness of this profile by professionals and caregivers can promote prompt diagnosis as well as early cognitive and occupational enhancement interventions.